Isolation and genetic characterization of a novel recombinant HP-PRRSV strain in Jiangxi Province, China - Wang, Chenyi; Li, Ruoming; Chen, Jiajia; Zhuo, Meiling; Peng, Qi; Kong, Lingbao; Wang, Ting (Frontiers in Veterinary Science, 2025)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a major pathogen responsible for significant economic losses in the global pig industry, primarily causing reproductive failure in sows and respiratory diseases in piglets. In this study, we isolated a novel PRRSV strain, designated NC2023, from clinical samples collected in 2023 from a pig farm in Jiangxi Province, China. The virus was successfully propagated in Marc-145 cells and demonstrated consistent infectivity in iPAM cells. Comprehensive characterization of NC2023 was performed using RT-qPCR, Western blotting, IFA, electron microscopy, plaque purification, and whole-genome sequencing. Phylogenetic and homology analyses of the complete genome revealed that NC2023 belongs to lineage 8 of the PRRSV-2 subtype and forms an independent branch in the evolutionary tree. The genomic length of NC2023 is 15,321 nucleotides, and recombination analysis indicated it is a recombinant strain with specific genomic regions derived from strains JXA1, JXA1-R, and HUN4. Notably, NC2023 exhibits 15 unique amino acid mutations compared to other recombinant strains, along with a 395-amino-acid frameshift mutation in Nsp2. This study reports the isolation and characterization of an HP-PRRSV recombinant PRRSV-2 strain using Marc-145 and iPAM cells, providing key insights into the genetic variation and evolutionary dynamics of PRRSV. These findings contribute to a deeper understanding of PRRSV molecular epidemiology and have important implications for the development of effective control strategies and vaccines.